Enhancing nutritive value of palm kernel expeller through physical treatments for use as poultry feed ingredient - Roslan, Muhamad Akhmal Hakim (2019)
Poultry production in Malaysia is heavily dependent on imported feed ingredients. The palm kernel expeller (PKE) is a potential feed ingredient to sustain the poultry industry. However, PKE had to be treated before it could be incorporated in poultry feed to reduce the anti-nutritive factors like indigestible mannan, lignin and broken kernel shells.. Hence, this study aimed at reducing these factors of PKE by extrusion and static cling- electrostatic separation technique to reduce the mannan and broken shells, respectively, and to produce a poultry feed containing treated PKE with a potential for commercial application. Extrusion was conducted by using a custom made co-rotating twin-screw extruder and static cling–electrostatic separation by using a simple fabricated apparatus. Response surface methodology (RSM) was used to optimize both treatments. Extrusion of PKE at optimized conditions (temperature, 178 ºC; screw speed, 100 rpm; hopper speed, 5 Hz and PKE moisture, 75%), significantly (P<0.05) reduced non-starch polysaccharides from 63.3% to 57.6%, and crude fibre from 16.7% to 13.5%, and significantly (P<0.05) increased mannose, glucose, fructose, 1,4-β-D-mannobiose; 1,4- β-D-mannotriose; 1,4-β-D-mannohexaose and 1,4-β-D-mannopentaose content. The production rate of extruded PKE (EPKE) was 180 kg/h. The static cling–electrostatic method at optimized conditions (13% PKE moisture; <1.5 mm PKE particle size and 110 g/min feed rate), reduced shells, lignin and fibre of PKE from 8.0% to 1.6%; 15.8% to 8.1% and 17.1% to 10.2%, respectively, and increased crude protein from 16.5% to 18.4%. The production rate of less-shell PKE (LSPKE) was 50 kg/h. The study on the effects of control (0% PKE), UPKE (untreated), EPKE, LSPKE and ELSPKE at 10%, 20% and 30% inclusion rates in finisher diets (d 21-42) showed that growth performance of broilers (Cobb 500) fed 10% PKE (irrespective of treatments), 20% LSPKE and ELSPKE, were comparable to control birds. At 30% PKE inclusion, broilers performance was significantly (P<0.05) reduced. Birds fed PKE diets, irrespective of treatments and inclusion levels had lower LDL and total cholesterol, and similar villi height and crypt depth compared to control. At 30% PKE inclusion level, although energy metabolism was enhanced, as indicated by the up-regulation of hexokinase I and phosphofructokinase, but broilers growth performance did not improve. The feeding trial showed that broilers fed 25% or 30% LSPKE (grower feed, d 16-24), followed by 20% LSPKE (finisher feed, d 25-35) containing feed supplements 0.02% commercial enzymes and 0.30% humic acid), had comparable FI, BWG and FCR to broilers fed commercial feeds. Broilers fed 25% or 30% UPKE (grower feed, d 16-24) followed by 20% UPKE (finisher feed, d 25-35) showed significantly higher (P<0.05) FCR compared to birds fed commercial feeds. The cost of feeds for production of birds fed LSPKE feeds (2.27-2.29 RM/kg liveweight), was lower than those fed commercial feeds (2.36 RM/kg liveweight). The study showed that physical treatments enhanced the nutritive value of PKE and feeds containing 25-30% and 20% LSPKE as grower and finisher rations, respectively, could attain broilers growth performance comparable to broilers fed commercial feeds. These diets could be potential feeds for commercial poultry production.